Two-Phase Induction Motor Drives - Gholam Reza Arab Markadeh; Aioob Babasalari (Journal of Intelligent Procedures in Electrical Technology, 2010)
The lack of variable-speed drives for two (single) induction motor is a reality. This article attempts mainly to investigate the reasons for this lack of variable – speed drives. This paper deals with literature survey of various existing converter topologies, which have been proposed for adjustable speed single phase induction motor drives. Various converter topologies have been compared in this paper. Among these converter topologies, the adjustable frequency PWM inverter is the best choice for single-phase induction motor drives. However, adjustable-frequency drives have not been widely used with single-phase Induction motors. The open-loop constant V/F control law cannot be used with the single-phase induction motor drives as it is used with three phase motors. The variation of the operating frequency at lower speed range with constant load torque causes variation in motor's slip. A constant V/F control is suitable only over the upper speed range.